Risk factors, clinical features, and outcomes of patients with hypertrophic cardiomyopathy complicated by ischemic stroke: A single-center retrospective study - Lu, Jian-Feng; Fan, Ze-Xin; Li, Ying; Wang, Ze-Yi; Ma, Lin; Yuan, Bo-Yi; Yang, Ting-Ting; Liu, Pen-Ju; Liu, Guang-Zhi (Frontiers in Cardiovascular Medicine, 2022)
Objective: This study aimed to explore risk factors, clinical features, and prognosis of patients with hypertrophic cardiomyopathy (HCM) complicated by ischemic stroke (IS). Methods: We conducted a retrospective analysis of all HCM patient data and a one-year follow-up study. Results:Totally, 506 patients with HCM, including 71 with IS, were enrolled. Older age (≥ 63 years) was associated with an increased risk of IS in HCM patients (OR = 1.045, 95% CI: 1.018–1.072, P = 0.001). Among 37 patients complicated by IS, 22 (59.5%, 22/37) manifested as cardioembolism (CE) subtype, and 13 (35.1%, 3/37) small artery occlusion (SAO) subtype, according to TOAST classification. Multi-infarction was more common than single infarction (72.7% vs. 27.3%), while cortical + subcortical infarction (CE group: 50%) or subcortical infarction (SAO group: 53.8%) constituted most IS cases. Additionally, the blood supply areas of anterior circulation (CE group: 45.5%; SAO group: 92.3%) or anterior + posterior circulation (CE group: 50%) were mainly involved. The one-year survival rate of HCM patients with concomitant IS was 81.8% and IS was associated with one-year all-cause death in HCM patients (HR = 5.689, 95% CI: 1.784–18.144, P = 0.003). Conclusion: Older age is a risk factor for IS occurrence in HCM patients. CE and SAO subtypes predominate in patients with concomitant IS, especially the former. Multiple cortical and subcortical infarctions are their neuroimaging characteristics, mainly involving the anterior circulation or anterior + posterior circulation. IS is a risk factor for all-cause death in HCM patients within one year.